2023
DOI: 10.1039/d2nj05475b
|View full text |Cite
|
Sign up to set email alerts
|

Hollow metal composite phosphides derived from MOFs as highly efficient and durable bifunctional electrocatalysts for water splitting

Abstract: Explore efficient non-precious electrocatalysts with dual functionality for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline solution are critical and challenging. Herein, hollow Fe2P @...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The XRD pattern (Figure i) of NFP reveals distinctive peaks at 40.79°, 44.64°, 47.44°, and 54.27 °Corresponding to the (111), (201), (210), and (300) crystal planes of Ni 2 P (JCPDS No. 03-0953). Furthermore, the peaks at 31.22°, 35.65°, 40.14°, 44.33°, 47.26°, and 54.52 ° correspond to the (101), (200), (111), (201), (210), (211) crystal planes of Fe 2 P (JCPDS No. 27-1171), respectively. EDS elemental mapping was conducted to delve deeper into the elemental distribution of the NFP, the results revealed a uniform distribution of the elements Fe, Ni, C, N, and P within the cubes (Figure j), and the presence of element C in it is due to the decomposition of CN – , which improves the electrical conductivity of the NFP .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD pattern (Figure i) of NFP reveals distinctive peaks at 40.79°, 44.64°, 47.44°, and 54.27 °Corresponding to the (111), (201), (210), and (300) crystal planes of Ni 2 P (JCPDS No. 03-0953). Furthermore, the peaks at 31.22°, 35.65°, 40.14°, 44.33°, 47.26°, and 54.52 ° correspond to the (101), (200), (111), (201), (210), (211) crystal planes of Fe 2 P (JCPDS No. 27-1171), respectively. EDS elemental mapping was conducted to delve deeper into the elemental distribution of the NFP, the results revealed a uniform distribution of the elements Fe, Ni, C, N, and P within the cubes (Figure j), and the presence of element C in it is due to the decomposition of CN – , which improves the electrical conductivity of the NFP .…”
Section: Resultsmentioning
confidence: 99%
“…03-0953). Furthermore, the peaks at 31.22°, 35.65°, 40.14°, 44.33°, 47.26°, and 54.52 ° correspond to the (101), (200), (111), (201), (210), (211) crystal planes of Fe 2 P (JCPDS No. 27-1171), respectively. EDS elemental mapping was conducted to delve deeper into the elemental distribution of the NFP, the results revealed a uniform distribution of the elements Fe, Ni, C, N, and P within the cubes (Figure j), and the presence of element C in it is due to the decomposition of CN – , which improves the electrical conductivity of the NFP . The specific surface area and pore structure of NiFe-PBA and NFP were calculated using the BET method (Figure S2a,b).…”
Section: Resultsmentioning
confidence: 99%
“…However, it showed better OER efficiency with lower overpotential, small Tafel slope, and high stability. Beside this, the nanospindle catalyst displayed efficient HER activity with an overpotential of 376 mV and small Tafel slope and also facilitated the electrolyte-transfer process and improved the active sites . Based on MOFs’ unique properties, Fan et al synthesized 3D cadmium-based MOFs which showed both functions: electrocatalytic oxygen evolution in water-splitting reactions and photocatalytic elimination of organic contaminants.…”
Section: Insights On Mofs and Applicationsmentioning
confidence: 99%
“…91 Based on MOFs' unique properties, Fan et al synthesized 3D cadmium-based MOFs which showed both functions: electrocatalytic oxygen evolution in water-splitting reactions and photocatalytic elimination of organic contaminants. The synthesis of a series of cadmium-based MOFs such as [Cd(bimb) 2 (HITA) 2 ] n and [Cd(bimb) 4 (ONO 2 ) 2 ] n revealed that the former exhibits excellent performance in OER with a lower overpotential of 279 mV and a reduced Tafel slope.…”
mentioning
confidence: 99%